Experimental and numerical investigation of damping in a hybrid automotive damper combining viscous and multiple-impact mechanisms. (December 2022) - Badri, Yousif; Sassi, Sadok; Hussein, Mohammed; Renno, Jamil
One of the least investigated approaches in passive vibration control is the possibility of combining different types of dampers that use different damping principles. Such a combination process, if wisely designed and implemented, has the potential to increase the damping performance and extend the damper's application. The primary purpose of this work is to experimentally and numerically investigate the damping behavior of a novel Fluid-Impact Hybrid Damper. This damper combines a conventional Viscous Fluid Damper with a Particle-Impact Damper. The Fluid-Impact Hybrid Damper comprises a 3D-printed plastic box attached to the Viscous Fluid Damper's moving rod and filled with stainless steel balls. An experimental setup was designed to drive the Viscous Fluid Damper's rod into harmonic oscillations at different frequencies (1, 2, 4, 6, and 8 Hz). The number of balls was changed three times (5, 10, and 15) to assess the effect of this parameter on the damping performance of the Fluid-Impact Hybrid Damper. A finite element model of the Fluid-Impact Hybrid Damper was developed using LS-Dyna explicit simulation program. The objective of the FE model is to investigate the elastoplastic balls-box collisions using a piecewise-linear plasticity material model. For both the experimental and numerical results, the Frequency Response Function was considered as the main comparison component for a set of force-independent results. The measured Frequency Response Functions showed a noticeable reduction in amplitude at the system's natural frequency (2 Hz), with an acceptable accuracy between the two approaches.